Herbal Health Communication Patterns in the Family to Improve Capacity Family Health Empowered Facing COVID-19 Pandemic - Suharti, Bangun; Trenggono, Nanang; Noviera, Fri Rejeki; Faizal, Ahmad Riza; Ulhaq, Abdullah Wildan (Universitas Nusa Cendana, 2024)
This research is important to do, because Indonesia is a very abundant and potential source of medicinal plants (herbs). Herbal-based medicine that is communicated and socialized, will be able to empower people in overcoming their health problems, especially during the Covid-19 pandemic. This is in line with the spirit of the community to return to nature, where people realize that the use of chemical drugs in large quantities and in the long term is actually harmful to health. This research is a qualitative research. Data collection methods were carried out by interview, observation and literature study. Interviews were conducted with 10 families, especially mothers who actively use herbs in Bandar Lampung city. The results of this study prove that herbal-based family health communication carried out using networks between friends, between environmental activist communities, herbal activists and herbal consultations using whatshap media and telegram groups, is very effective as a means of promoting family health, so that families are health independent. The role of mothers is very important in opening opportunities for promotion and family awareness, on the importance of herbs, as a solution to family health problems. This is supported by the right moment, when the whole world is hit by problems, crises, and major challenges in the health sector, namely the Covid-19 pandemic.